ENTREPRENEURIAL SELF-EFFICACY (ESE) DAN PERANNYA TERHADAP KEBERTAHANAN BISNIS - Chris Petra Agung; Teresia Debby; Ignasia Tiffani; Budiana Gomulia (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
The number of micro, small, and medium enterprises (MSMEs) in West Java is constantly increasing during 2016-2021 period. Many of them are new ventures which are in the process of introducing their products or services to the market; or are developing their customer base. Previous researches find that new venture viability is determined by owner-manager’s Entrepreneurial Self-Efficacy (ESE). This research aims to analyse three factors that are thought to influence ESE, namely: formal education of entrepreneurship (PFK), family support (DK), and entrepreneurial personality (EP). Furthermore, the effect of ESE to new venture viability will be tested. The samples used in this research are graduate of Bachelor of Management program, X Private University in Bandung Municipality who have undertaken Entrepreneurship courses and owned and managed his or her own business. Data is collected through close-ended questionnaires and is processed using SEM-PLS. Thereafter, a Focus Group Discussion (FGD) was conducted to validate the statistical results. The research finds that: (1) EP significantly and positively affects ESE, and (2) ESE significantly and positively affects new venture viability. Keywords: entrepreneurial self-efficacy (ESE); entrepreneurial personality; new venture viability. Jumlah usaha mikro, kecil, dan menengah (UMKM) di Jawa Barat terus meningkat selama periode 2016-2021. Banyak dari pelaku UMKM tersebut adalah usaha mula-mula yang berada pada tahap memperkenalkan produk atau jasa yang ditawarkan ke pasar atau sedang memperkuat basis pelanggan. Beberapa penelitian terdahulu menyimpulkan bahwa kebertahanan usaha mula-mula dipengaruhi oleh Entrepreneurial Self-Efficacy (ESE) pemilik-pengelola usaha. Penelitian ini bertujuan untuk menganalisis tiga faktor yang diduga memengaruhi ESE yakni: pendidikan formal kewirausahaan (PFK), dukungan keluarga (DK), dan entrepreneurial personality (EP). Selanjutnya, penelitian ini akan menguji pengaruh ESE terhadap kebertahanan usaha mula-mula. Sampel dari penelitian ini adalah alumni program Studi Manajemen, Perguruan Tinggi Swasta (PTS) X di Kota Bandung yang telah mengambil mata kuliah kewirausahaan serta memiliki dan mengelola usaha sendiri. Pengambilan data menggunakan kuesioner close-ended dan teknik pengolahan data menggunakan SEM-PLS. Setelah itu, Focus Group Discussion (FGD) dilakukan untuk memvalidasi hasil pengolahan data secara statistik. Hasil penelitian menunjukkan bahwa: (1) EP berpengaruh positif dan signifikan terhadap ESE; dan (2) ESE berpengaruh positif dan signifikan terhadap kebertahanan usaha mula-mula. Kata kunci: entrepreneurial self-efficacy (ESE); entrepreneurial personality; kebertahanan usaha mula-mula.